VALIAÇÃO DO CRESCIMENTO DOS CLONES I-144 E 1277 DE EUCALIPTO NO MUNICÍPIO DE AQUIDAUANA – MS - VERA, Damaris Elias; GOUVÊA, Adriana de Fátima Gomes; CACAU, Filipe Valadão do Prado; TEIXEIRA, Gabriel Dias (ANAIS DO ENIC, 2017)
-